ANALISIS HUBUNGAN ANTARA DUKUNGAN PSIKOSOSIAL DENGAN PERILAKU KEBERHASILAN PENGOBATAN PASIEN TB DI KOTA SEMARANG - Nafiah Yusi; Laksmono Widagdo; Kusyogo Cahyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Success rate of TB in Semarang in 2013-2016 was 83%, this figure showed that the target set by the Central Java Provincial Health Office has not been 90%. Importance psychosocial offers for TB sufferers such as taking TB drugs regularly, motivating to achieve recovery, and providing information for TB patients will use TB to achieve treatment success. The basic things needed by TB patients are the psychological and social. Research to analyze the relationship between psychosocial use of TB services in the city of Semarang. This research is an analytical study using cross sectional study. The sampling technique used in this study is to use a total sampling that is silent 49 people. Data analysis in this study uses univariate and bivariate analysis. The results showed that most respondents had good TB success behavior of 63.3%. Based on the results of bivariate analysis using Chi-square test showed that there were relationship between knowledge of TB treatment (p-value = 0,000), family support for TB treatment (p-value = 0,031), PMO support for TB treatment (p-value = 0,031), and medical staff support for TB treatment (p-value = 0.029) with behaviors of successful treatment of TB patients in Semarang.